DEVELOPMENT OF TEACHING MATERIALS BASED ON STRENGTHENING THE PANCASILA PROFILE OF SCIENCE AND SCIENCE SUBJECTS TO IMPROVE CRITICAL-CREATIVE - Sri Suryaningsih; Arwan; Nur'aini Rahma (Jurnal Cakrawala Pendas, 2024)
The independent learning curriculum has its challenges for every teacher. The selection of models that support the independent curriculum is not yet appropriate and teaching materials to train critical-creative skills are not yet optimal. Therefore, it is necessary to develop teaching materials with the PjBL model to improve students' critical and creative thinking. The research aims (1) to determine the suitability of teaching materials, (2) the practicality of teaching materials, and (3) the effectiveness of teaching materials. The research method uses R & D (Research and Development) adopted by Borg & Gall with 10 stages. The instruments used were teacher response questionnaires, student response questionnaires, critical skills tests, and creative skills tests. The research subjects were 103 students at Elementary School 1 Kaleo, Elementary School 2 Kaleo, and Elementary School Inpres Kaleo. The teaching materials are suitable for use according to the expert validator's assessment category, namely very valid and valid. The practicality of the teaching materials is very good based on the results of the teacher and student response questionnaire. Effective teaching materials to improve students' critical-creative skills The development of PjBL teaching materials based on strengthening the Pancasila profile in the subject of science and science to improve the critical-creative skills of elementary school students is suitable for use and can improve critical-creative skills.